Measurement of Work Fatigue in Dump Truck Operator at PT. AX, Tenggarong, Indonesia - Laura Nisa Elvira; Vita Pramaningsih; Deny Kurniawan (Poltekkes Kemenkes Tanjung Karang, 2025)
Job burnout is a form of work fatigue resulting from work stress , which can manifest as emotional, physical , and mental exhaustion followed by decreased performance . This study aimed to measure job fatigue among PT. AX employees. Data collection was conducted through interviews using a questionnaire. This descriptive study was conducted from February to March 2024. The sample consisted of 80 dump truck operators at PT. AX who were randomly selected. The variables measured included work fatigue level , worker age, length of service , and number of working hours. The results of the study showed that most (80.0%) respondents had less than 10 years of work experience, were less than 31 years old (69.5%), and had eight-hour working hours (46.25%). Although the majority of workers (72.5%) experienced moderate fatigue, 2.5% of workers were found to be in the severe category. Symptoms of fatigue experienced by operators were eye fatigue, and signs of fatigue were seen while driving, such as pain in the lower back, frequent yawning, and frequent thirst. This study found that most dump truck operators at PT AX experienced moderate (72.5%) and severe (2.5%) fatigue.